Adsorption of rhodamine B and methylene blue dyes using waste of seeds of Aleurites Moluccana, a low cost adsorbent - Debora Luiza Postai; Carla Albertina Demarchi; Francielle Zanatta; Danielle Caroline Cipriani Melo; Clóvis Antonio Rodrigues (Alexandria Engineering Journal, 2016)
Removal of the cationic dyes rhodamine B (RhB) and methylene blue (MB) by waste seeds Aleurites moluccana (WAM) was studied in a batch system. The adsorbent was characterized by Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), point of zero charge measurement, and the Boehm titration method. The effects of contact time and pH were investigated for the removal of cationic dyes. An increase in pH from 3 to 9 was accompanied by an approximately three-fold increase in the amount of dye adsorbed. The adsorptions equilibrium values were obtained and analyzed using the Langmuir, Freundlich, Sips, and Redlich–Peterson equations, the Sips isotherm being the one that showed the best correlation with the experimental values. The maximum adsorption capacities of the dyes were 178 mg/g for the MB and 117 mg/g for the RhB. The kinetic sorption was evaluated by the pseudo-first-order, pseudo-second-order, and intraparticle diffusion models, where it was observed that sorption follows the pseudo-second-order kinetic model. The study of thermodynamics showed that the adsorption is a spontaneous and endothermic process. The results indicate that waste seeds of A. moluccana could be used as a low cost material for the removal of cationic dyes from wastewater.